Genes implicated in stem cell identity and temporal programme are directly targeted by Notch in neuroblast tumours - Zacharioudaki, Evanthia (Development, 2016)
Notch signalling is involved in a multitude of developmental decisions and its aberrant activation is linked to many diseases, including cancers. One example is the neural stem cell tumours that arise from constitutive Notch activity in Drosophila neuroblasts. To investigate how hyperactivation of Notch in larval neuroblasts leads to tumours, we combined results from profiling the upregulated mRNAs and mapping the regions bound by the core Notch pathway transcription factor Su(H). This identified 246 putative direct Notch targets. These genes were highly enriched for transcription factors and overlapped significantly with a previously identified regulatory programme dependent on the proneural transcription factor Asense. Included were genes associated with the neuroblast maintenance and self-renewal programme that we validated as Notch regulated in vivo. Another group were the so-called temporal transcription factors, which have been implicated in neuroblast maturation. Normally expressed in specific time windows, several temporal transcription factors were ectopically expressed in the stem cell tumours, suggesting that Notch had reprogrammed their normal temporal regulation. Indeed, the Notch-induced hyperplasia was reduced by mutations affecting two of the temporal factors, which, conversely, were sufficient to induce mild hyperplasia on their own. Altogether, the results suggest that Notch induces neuroblast tumours by directly promoting the expression of genes that contribute to stem cell identity and by reprogramming the expression of factors that could regulate maturity.